2020
DOI: 10.1016/s2666-5247(20)30059-8
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin susceptibility of Neisseria gonorrhoeae in the USA in 2017: a genomic analysis of surveillance data

Abstract: BackgroundThe number of cases of gonorrhoea in the USA and worldwide caused by Neisseria gonorrhoeae is increasing (555 608 reported US cases in 2017, and 87 million cases worldwide in 2016). Many countries report declining in vitro susceptibility of azithromycin, which is a concern because azithromycin and ceftriaxone are the recommended dual treatment in many countries. We aimed to identify strain types associated with decreased susceptibility to azithromycin. MethodsWe did a genomic analysis of N gonorrhoea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 24 publications
3
56
0
Order By: Relevance
“…Accordingly, we hypothesize that any influence A39T might have on mtrCDE depression requires the presence of other MtrR amino acid changes common in clinical strains such as R44Q or Y48D substitution ( 4 ); as shown in our fluorescence polarization-based DNA binding studies, R44 and Y48 are critical for high affinity DNA binding (Table 3 and Supplementary Figure S5 ). This hypothesis is further supported by the high frequency of accompanying mutations in clinical isolates of N. gonorrhoeae containing the A39T mutation ( 57 ) ( Supplementary Table S6 ).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Accordingly, we hypothesize that any influence A39T might have on mtrCDE depression requires the presence of other MtrR amino acid changes common in clinical strains such as R44Q or Y48D substitution ( 4 ); as shown in our fluorescence polarization-based DNA binding studies, R44 and Y48 are critical for high affinity DNA binding (Table 3 and Supplementary Figure S5 ). This hypothesis is further supported by the high frequency of accompanying mutations in clinical isolates of N. gonorrhoeae containing the A39T mutation ( 57 ) ( Supplementary Table S6 ).…”
Section: Resultsmentioning
confidence: 71%
“…Further, both mutations similarly elevated expression of mtrC and rpoH (Figure 4 ). These mutations could contribute to resistance in gonococcal isolates in tandem with other mtrR point mutations as suggested by the occurrence of accompanying mutations in the HTH motif or mtrCDE operator in a recent survey of clinical isolates in the USA ( 57 ) ( Supplementary Table S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…As described above, other mechanisms have also been recently discovered that increase the MIC of azithromycin (Table 2 ), such as mosaicism affecting the efflux pump-encoding mtrCDE genes and its repressor mtrR , mainly when the mosaic spans the mtrR promoter region and mtrD gene [ 23 , 24 ]. Some studies have recently reported the local expansion of azithromycin-resistant N. gonorrhoeae lineages carrying an mtr mosaic in the USA [ 122 , 123 , 134 ] and Australia [ 118 ]. However, the extent of the dispersion of this mechanism to other parts of the world has not been studied yet.…”
Section: Resultsmentioning
confidence: 99%
“…During 2018, among men who have sex with men, the proportion of GISP isolates with an azithromycin alert value was 8.6%, compared with 2.9% among men who have sex with women only ( 1 ). Studies have associated development of reduced azithromycin susceptibility with azithromycin exposure among patients with N. gonorrhoeae infection ( 24 , 25 ).…”
Section: Evidence and Rationalementioning
confidence: 99%